Involvement of caveolin-1 in skin diseases - Takamura, Naoko; Yamaguchi, Yukie (Frontiers in Immunology, 2022)
The skin is the outermost layer and largest organ in the human body. Since the skin interfaces with the environment, it has a variety of roles, including providing a protective barrier against external factors, regulating body temperature, and retaining water in the body. It is also involved in the immune system, interacting with immune cells residing in the dermis. Caveolin-1 (CAV-1) is essential for caveolae formation and has multiple functions including endocytosis, lipid homeostasis, and signal transduction. CAV-1 is known to interact with a variety of signaling molecules and receptors and may influence cell proliferation and migration. Several skin-related disorders, especially those of the inflammatory or hyperproliferative type such as skin cancers, psoriasis, fibrosis, and wound healing, are reported to be associated with aberrant CAV-1 expression. In this review, we have explored CAV-1 involvement in skin physiology and skin diseases.